أثر اختيار نظام الصرف ووضعية حساب رأس المال على سلوك الاحتياطات الدولية في الدول النامية – دراسة قياسية باستخدام نماذج معطيات Panel- - محمد, أ. ترقو (Recherches économiques et managériales, 2015)
ملخص:   تهدف الدراسة إلى اختبار أثر اختيار أنظمة الصرف ووضعية حساب رأس المال على سلوك الاحتياطات الدولية في الدول النامية خلال الفترة 2005-2012، حيث تم اختيار عينة مكونة من 113 دولة نامية تمثل نسب احتياطاتها الدولية في حدود (56%-67%) من إجمالي الاحتياطات الدولية في كل دول العالم، وتم استخدام نماذج معطيات Panel بالتطبيق على النموذج المقترح من طرف Aizenman و L e e سنة 2007، وخلصت الدراسة إلى أن نموذج الأثر الثابت للدول يعتبر أحسن نموذج مقدر وخلص هذا النموذج إلى عدم وجود أي تأثير لوضعية حساب رأس المال وتقلبات أسعار الصرف على الاحتياطات الدولية، وبالتالي يمكن استخلاص أن تغيرات احتياطات الصرف في الدول النامية ليس نتاج وضعية حساب رأس المال (الفائض أو العجز) أو طبيعة نظام الصرف المتبع في الدولة (تثبيت أو تعويم). الكلمات المفتاحية: نظام الصرف، حساب رأس المال، الاحتياطات الدولية، نموذج Aizenman و L e e ، الدول النامية. Abstract:            This study aims to test the effect of exchange rate regime choosing and the capital account situation on the international reserves behavior in developing countries during 2005-2012, we select a sample of 113 developing countries, their international reserves ratios representing between 56%  and 67% of the total international reserves in all countries of the world, we used the Panel data models by applying on the model proposed by Aizenman and Lee in 2007, we concluded to the result that the fixed effect of the States model is a better model and the absence of any effect of the status of the capital account and exchange rate fluctuations on international reserves, and can therefore conclude that the changes in the foreign exchange reserves in developing countries is not a result of the status of the capital account (surplus or deficit) or the nature of the exchange rate regime followed in the state (fix or float). Keywords: exchange rate regime, capital account, international reserves, Aizenman and Lee model, developing countries .